Merging nanocommunications topics in the electrical and network engineering programs of Peruvian Universities - Nieto Chaupis, Huber (2017)
The imminent arrival of advanced technologies in the field of telecommunications would give impulse to upgrade coherently the content of the topics of the last year of the electrical and network engineering program. For instance, the new topics based on the so-called nanocommunications networks might play a crucial role in the field of the medicine. It would demand to implement dedicate networks to be running in an unstoppable manner. In this paper, we present a possible content with a duration of 16 weeks or 4 months with a previous preparation of topics based on a 18-hours per week. All this scheme would provide capabilities to face new fields in the side of the nanocommunications to be applied inside of the nanotechnlogy and nanomedicine, fact that would empower the prospective bachelor of the electrical and network engineering program.